1989
DOI: 10.1007/bf00199107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anticancer agents neothramycin, aclacinomycin, FK-565 and FK-156 on the release of interleukin-2 and interleukin-1 in vitro

Abstract: Four anticancer agents, neothramycin, aclacinomycin, FK-565 and FK-156, were tested for their effects on concanavalin-A-induced interleukin-2 release from rat splenocytes in vitro. Neothramycin showed an enhancement of the release of interleukin-2, whereas aclacinomycin had no effect. FK-565 and FK-156 were found to inhibit the release of interleukin-2 under similar conditions. The inhibition was much more marked with FK-565. These drugs were also tested for their effects on the release of interleukin-1 from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…MDP and several other adjuvant-active analogs induce high levels of membranebound IL-1 in mouse peritoneal macrophages; in contrast, adjuvant-inactive analogs, such as MDP containing D-Ala, are unable to trigger IL-1 production (16). FK-565 and FK-156 also induce the release of IL-1 from lipopolysaccharide-stimulated rat peritoneal exudate cells (29). In keeping with this pattern,…”
Section: Discussionsupporting
confidence: 65%
“…MDP and several other adjuvant-active analogs induce high levels of membranebound IL-1 in mouse peritoneal macrophages; in contrast, adjuvant-inactive analogs, such as MDP containing D-Ala, are unable to trigger IL-1 production (16). FK-565 and FK-156 also induce the release of IL-1 from lipopolysaccharide-stimulated rat peritoneal exudate cells (29). In keeping with this pattern,…”
Section: Discussionsupporting
confidence: 65%
“…They are known to increase resistance to microbial infections and are associated with inereased tumoricidal activity of macrophage [15,13]. Increased T N F production in vitro by FK565 correlates with out previous report of enhancement of IL-1 in vitro by this drug [4]. In this study FK156 did not significantly alter the release of T N F although it enhanced IL-1 release in vitro in out previous work.…”
Section: Discussionsupporting
confidence: 91%
“…We have shown an enhancement of the release of IL-2 in vitro and in vivo by Adriamycin and bleomycin, and inhibition of IL-2 by vincristine, vinblastine and cyclophosphamide under similar conditions [1][2][3]5]. We have also reported that the release of IL-1 is increased in vitro by Adriamycin, bleomycin, and the experimental peptides FK565 and FK156 [2][3][4].…”
Section: Introductionmentioning
confidence: 73%
“…These compounds did not alter the release of IL-6 in these experiments. In earlier studies these peptides had increased the release of IL-1, and FK565 induced enhanced TNF release from rat macrophages [2,15], whilst IL-2 release from spleen cells was reduced by the peptides [2]. Interferon y and IL-3 have not been affected by these compounds [4,14].…”
Section: Discussionmentioning
confidence: 88%